Արևելյան լեզուներից անցած փոխառությունները Գորիսի բարբառում (ըստ Ս. Խանզադյանի «Մատյան եղելությանց» վիպակի) - Քումունց, Մհեր; Մարգարյան, Մարի (ՀՀ ԳԱԱ ԼԻ հրատ.)
Sero Khanzadyan’s novel "Log of existence" is rich in borrowings from Eastern languages, which have found a unique place in the Goris dialect. As a result of historical influences, these words have become an inseparable part of the dialect. The study focuses exclusively on words of Arabic, Persian, and Turkic origin, with explanations provided based on the original text and the Goris dialect, considering their usage features and semantic nuances. Роман Серо Ханзадяна "Летопись былого" богат восточными заимствованиями, которые нашли свое место в горийском диалекте. В результате исторических влияний эти слова стали неотъемлемой частью диалекта. Объектом исследования являются исключительно слова арабского, персидского и тюркского происхождения, значения которых были даны на основе оригинала и горийского диалекта, с учетом их употребления и смысловых оттенков.
Keywords: Բարբառագիտություն